Discrimination toward Asian Immigrant in United States in The Novel Quichotte (2019) by Salman Rushdie - Irma Permata; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2023)
This thesis is an analysis of the novel Quichotte (2019) by Salman Rushdie. The purpose of this analysis is to find out how the novel shows the issue of discrimination toward Asian Immigrant which is done by the American. This analysis also intended to show how the contribution of fictional elements (character, setting and action/plot) in revealing the issue of discrimination. This analysis is done through a text-based and context-based interpretation which related to the concept of orientalism by Edward R. Said. The result of this analysis shows the Asian Immigrant getting discriminate by the American. The discrimination can be seen through physical violence and verbal violence.